Електрохімічний синтез пористого кристалічного оксиду танталу - Водолажченко, Сергій Олександрович; Ляшок, Лариса Василівна; Гомозов, Валерій Павлович; Скатков, Л. І. (Дослідно-видавничий центр Наукового товариства ім. Шевченка, 2018)
In this study, the mechanism defined electrochemical synthesis AOP crystal structure, shown that the formation of AOS on tantalum flows through the solid phase polysurface mechanism of the formation of the lower valence oxides, which are the nuclei of a crystalline phase. The choice of electrolyte components for electrochemical synthesis of crystalline porous tantalum on AOP. The method of electrochemical impedance spectroscopy to determine the equivalent circuit elements, which characterize the basic properties of the synthesized AOP.
Electrochemical Synthesis of Portastic Crystalline Oxide of Tantal
Keywords: анодування; наноматеріали; оксид танталу; електрохімічний метод синтезу; tantalum; porous; oxide; morphology; anodizing; impedance; decoration